Ethnos Meets Eros on the River Plate: Marcelo Birmajer, Sylvia Molloy, Anna Kazumi Stahl - Edna Aizenberg (Studies in 20th & 21st Century Literature, 2005)
This article deals with three contemporary novelists, Marcelo Birmajer, Anna Kazumi Stahl and Sylvia Molly in the context of a new understanding of ethnicity, sexuality and literature in Argentina. In contrast to previous eras when writing reflected a melting pot philosophy which saw Eros as a means of fusing ethnicities and eliminating particularities, today's fiction often celebrates these differences, uncovering layers of secrecy and demanding a place for various languages, sexualities and geographies.
Keywords: Marcelo Birmajer; Anna Kazumi Stahl; Sylvia Molly; ethnicity; sexuality; literature in Argentina; Argentinian Literature; melting pot; melting pot philosophy; Eros; language; geography